KEPUTUSAN PEMBELIAN PELANGGAN TOKOPEDIA DI JAKARTA - Santi Septianingsih (2022)
This study is a quantitative study that aims to determine the effect of BTS brand ambassadors, buying interest, brand image on the purchasing decisions of Tokopedia customers in Jakarta. In this study, the population used is BTS fan customers who use Tokopedia in Jakarta with a total sample of 100 respondents. Probability sampling was taken using the cluster sampling method, which used PLS (Partial Least Square) version 3.3.7. Data was collected by distributing questionnaires via Google form. The results show that: (1) brand ambassador has a positive and significant effect of 0.389 on purchasing decisions (2) buying interest has a positive and significant effect of 0.389 on purchasing decisions (3) brand image has a positive and significant effect of 0.206 on purchasing decisions. While brand ambassadors, buying interest, brand image contributed 76.5% to purchasing decisions, while the remaining 23.5% was caused by other variables not included in this study such as, price, product quality, service quality, and other Keywoards: Brand Ambassador, Buying Interest, Brand Image, Purchase Decision